2016
DOI: 10.1159/000445985
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Helicobacter pylori</i></b>: Does Gastritis Prevent Colitis?

Abstract: Background: Since its discovery in the early 1980s, Helicobacter pylori has been linked to a variety of gastric and extragastric diseases. Chronic infection with H. pylori causes histologically evident gastritis in all colonized individuals and is the predominant risk factor for gastric and duodenal ulcers as well as gastric adenocarcinoma. However, increasingly robust experimental and epidemiological evidence suggests that H. pylori may at the same time be beneficial to its carriers, as it efficiently prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 94 publications
(169 reference statements)
0
12
0
Order By: Relevance
“…Additionally, several studies revealed that probiotic supplementation could reduce the antibiotic‐induced dysbiosis and decrease the frequency of adverse effects of H. pylori eradication therapy . In addition, there is emerging experimental and epidemiological evidence suggesting that H. pylori may be beneficial to its carriers by preventing the development of inflammatory bowel disease . Future research is warranted to clarify the benefits and risk of eradication therapy in the development of intestinal disorders and the relationships between alterations of the gut microbiota following eradication therapy and the risk of developing intestinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies revealed that probiotic supplementation could reduce the antibiotic‐induced dysbiosis and decrease the frequency of adverse effects of H. pylori eradication therapy . In addition, there is emerging experimental and epidemiological evidence suggesting that H. pylori may be beneficial to its carriers by preventing the development of inflammatory bowel disease . Future research is warranted to clarify the benefits and risk of eradication therapy in the development of intestinal disorders and the relationships between alterations of the gut microbiota following eradication therapy and the risk of developing intestinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility has been previously reported that the initiation of the human IBD can be triggered by other types of Helicobacter organisms from colon such as Helicobacter bilis, Helicobacter fennelliae, Helicobacter hepaticus, and Helicobacter trogontum. 7 Also, CagA positivity was higher in the patients with more active IBDs.…”
Section: Discussionmentioning
confidence: 95%
“…5,6 In recent years diagnosis of IBD cases are being increased. 7 At the same time with improved hygiene especially in developing countries, H.P infection in gastrointestinal tract is being decreased. 8 So, there are reports about protective effects of H.P infection and gastritis against IBD development.…”
Section: Discussionmentioning
confidence: 99%
“…Human CD8 + T-cells are emerging as major mediators of human IBD and the identification of a key role for Gab2/3 in suppression of T-cell and macrophage function, fills in major gaps in our understanding of how CD8 + T-cells drive IBD. Furthermore, the H. pylori virulence factor CagA has been shown to protect against DSS-induced experimental colitis ( 79 ) and is inversely associated with human IBD ( 40 ) but no functional roles have been previously attributed to Gab adaptor proteins in promoting a healthy colon under normal physiological conditions. The findings of this study thus provide a deeper understanding of how Gab2 and Gab3 redundantly function to ultimately control CD8 + T-cell and this finding could lead to new therapeutic avenues.…”
Section: Discussionmentioning
confidence: 99%